2012
DOI: 10.1517/17425255.2012.678048
|View full text |Cite
|
Sign up to set email alerts
|

Impact of drug transporter pharmacogenomics on pharmacokinetic and pharmacodynamic variability – considerations for drug development

Abstract: Unlike polymorphisms for cytochrome P450s (CYPs) resulting in large magnitude of PK variation, genetic mutations for membrane transporters are typically less than threefold alteration in systemic PK for drugs with a few exceptions. However, substantially greater changes in intracellular drug levels may result. We are aware of 1880 exome variants in 12 of the best-studied transporters to date, and nearly 40% of these change the amino acid. However, the functional consequences of most of these variants remain to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 122 publications
1
26
0
Order By: Relevance
“…For example, atorvastatin has a high extent of metabolism (>90% of parent eliminated as metabolites), however, active uptake mediated by organic anion transporting polypeptide (OATP) transporters is the rate-determining step of its clearance [12]. Similar evidences were reported with bosentan, cerivastatin, fluvastatin, and repaglinide [5][6][7][8][9][10][11]. In addition, compounds such as valsartan and rosuvastatin are predominantly excreted unchanged in bile while active uptake mediated by OATP transporters is the rate-determining step of their clearance.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…For example, atorvastatin has a high extent of metabolism (>90% of parent eliminated as metabolites), however, active uptake mediated by organic anion transporting polypeptide (OATP) transporters is the rate-determining step of its clearance [12]. Similar evidences were reported with bosentan, cerivastatin, fluvastatin, and repaglinide [5][6][7][8][9][10][11]. In addition, compounds such as valsartan and rosuvastatin are predominantly excreted unchanged in bile while active uptake mediated by OATP transporters is the rate-determining step of their clearance.…”
Section: Introductionmentioning
confidence: 67%
“…It should be emphasized that a drug's predominant elimination process such as metabolism, biliary or renal excretion may not be always its ratedetermining step in systemic clearance -the latter being the determinant of systemic drug exposure [5][6][7][8][9][10][11]. For example, atorvastatin has a high extent of metabolism (>90% of parent eliminated as metabolites), however, active uptake mediated by organic anion transporting polypeptide (OATP) transporters is the rate-determining step of its clearance [12].…”
Section: Introductionmentioning
confidence: 99%
“…A recent report showed significant loss in transporter expression and activity in human cryopreserved hepatocytes compared with fresh hepatocytes and may contribute to the in vitro-in vivo disconnect (Lundquist et al, 2014). Genetic polymorphism in SLCO1B1, particularly homozygous OATP1B1*15 variant, was reported to possess reduced transport activity (Nishizato et al, 2003;Niemi et al, 2011;Lai et al, 2012;Tomita et al, 2013), and the hepatocytes with such variant may underpredict in vivo clearance. Further investigation in these areas is warranted to understand the lower functional activity in the in vitro systems (Barton et al, 2013;Zamek-Gliszczynski et al, 2013;Li et al, 2014;Lundquist et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…1980 Di et al through transporter genetic polymorphism and drug interaction studies, where significant changes in the pharmacokinetics of some drugs and consequent clinical responses are observed (Niemi et al, 2005;Giacomini et al, 2010;Niemi et al, 2011;Elsby et al, 2012;Lai et al, 2012). A number of studies suggested that hepatic uptake could be a rate-determining step in hepatic clearance, not only for the compounds that are metabolically stable, such as rosuvastatin (Bergman et al, 2006) and pravastatin, (Yamazaki et al, 1996;Watanabe et al, 2009a;Varma et al, 2012c), but also for compounds that are extensively metabolized, e.g., repaglinide (Kalliokoski et al, 2008;Varma et al, 2013b) and atorvastatin .…”
Section: Predicting Clearancementioning
confidence: 99%